Causes of Neonatal Death in Ayder Comprehensive Specialized Hospital, Ethiopia - Fikaden Berhe Hadgu; Gebregziabher Berihu Gebrekidan (Mashhad University of Medical Sciences, 2020)
Background: The first 28 days of life are the most sensitive time regarding a child's survival and health. Neonatal death accounts for a major part of under-five deaths, especially in sub-Saharan Africa. In this regard, the present study aimed to identify the causes of neonatal deaths in Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia.Methods: The present institution-based descriptive cross-sectional study was conducted on neonates admitted to the neonatal intensive care unit of Ayder Comprehensive Specialized Hospital from June 2018 to May 2019. The required data were extracted from the medical charts of the patients during admission and discharge and their death certificates. The collected data were analyzed in SPSS software (version 23) using descriptive statistics to describe the prevalence and causes of neonatal deaths. The final results were summarized using frequencies and proportions.Results: In total, 1785 neonates were admitted during the study period and 1388 (77.8%), 99 (5.5%), and 298 (167 per 1000 live births) of them were treated and discharged, discharged against medical advice, and died, respectively. The causes of 139 (46.6%), 72 (24.2%), 63 (21.1%), and 22 (7.4%) neonatal deaths in the hospital were prematurity- related complications, neonatal sepsis, perinatal asphyxia, and congenital anomalies, respectively. The highest mortality rate was observed in neonates with respiratory distress syndrome since 89 out of 127 (70.8%) afflicted neonates died. Moreover, the second-highest mortality rate was found in newborns with perinatal asphyxia as 63 out of 174 (36.2%) afflicted newborns died. Furthermore, it was found that almost all deaths (98.3%) occurred during the first seven days after birth.Conclusion: Based on the results, it can be concluded that the neonatal mortality rate was substantially high among the studied neonates. Moreover, the case fatality rate of respiratory distress syndrome was alarmingly high. Therefore, all the people who are in charge must devote a considerable effort to improve the health care delivered to neonates.